Fluorogenic Granzyme A Substrates Enable Real‐Time Imaging of Adaptive Immune Cell Activity. (16th January 2023) - Cheng, Zhiming; Thompson, Emily J; Mendive‐Tapia, Lorena; Scott, Jamie I; Benson, Sam; Kitamura, Takanori; Senan‐Salinas, Ana; Samarakoon, Youhani; Roberts, Edward W; Arias, Maykel A; Pardo, Julian; Galvez, Eva M; et al.
Abstract: Cytotoxic immune cells, including T lymphocytes (CTLs) and natural killer (NK) cells, are essential components of the host response against tumors. CTLs and NK cells secrete granzyme A (GzmA) upon recognition of cancer cells; however, there are very few tools that can detect physiological levels of active GzmA with high spatiotemporal resolution. Herein, we report the rational design of the near‐infrared fluorogenic substrates for human GzmA and mouse GzmA. These activity‐based probes display very high catalytic efficiency and selectivity over other granzymes, as shown in tissue lysates from wild‐type and GzmA knock‐out mice. Furthermore, we demonstrate that the probes can image how adaptive immune cells respond to antigen‐driven recognition of cancer cells in real time. Abstract : We describe NIR fluorogenic substrates for granzyme A with rapid responses and enzyme sensitivity at physiological levels. We demonstrate that these probes can be used for real‐time imaging of CTLs and NK cells in co‐cultures with cancer cells and in ex vivo tissues, opening new avenues to monitor the functions of the immune system in the tumor microenvironment.